Perlindungan Hak Cipta Di Era Digital Dalam Perspektif Cyber Law - Aulia Rahmadina; Romi Faslah (Jurnal Ekonomi dan Bisnis Digital, 2025)
The rapid development of digital technology has presented new challenges in copyright protection. Copyrighted works are now easy to reproduce and disseminate through the internet, causing the risk of copyright infringement, such as piracy and unauthorised use of works. This article discusses the concept of copyright, the registration process, and the relevance of legal protection within the framework of Law No. 28 of 2014 on Copyright and the Law on Information and Electronic Transactions (UU ITE). This research uses a descriptive qualitative approach with a literature study method. The results of this study show that although regulations already exist, the effectiveness of copyright protection in the digital era still faces various obstacles, including weak law enforcement, low public awareness, and the complexity of information technology. Therefore, a synergy between adaptive legal regulations, strict law enforcement, and the active role of the community in protecting copyright is needed. Cyber law is an important foundation to protect digital works and encourage the growth of a healthy and sustainable creative industry in Indonesia.